Dampak Pandemi Covid-19 Terhadap Perkembangan Pendidikan - Imade Rai Murdana (Prodi PGSD Unsultra, 2021)
During the Covid-19 pandemic, education in Indonesia was carried out online from home to prevent and reduce the spread of the virus. However, in several regions, offline learning was also implemented due to limited internet access. Therefore, this scientific paper aims to describe the development of education in Indonesia during the Covid-19 pandemic and to provide appropriate solutions for online learning. The research method used is a literature study, obtained from documents, articles, and news related to online learning during the pandemic. The collected data were analyzed using a descriptive method, which seeks to reveal facts and events written in statements derived from the data sources studied. The results of this study explain the processes and challenges faced during online learning. In addition, it provides several suggestions to overcome existing problems in online learning during the Covid-19 pandemic. Online learning became one of the most effective solutions to ensure that education in Indonesia continued to function properly and achieve its intended learning objectives during the pandemic.